2017
DOI: 10.1007/s12672-017-0287-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher Dihydrotestosterone Is Associated with the Incidence of Lung Cancer in Older Men

Abstract: Advancing age is associated with increased cancer incidence, but the role of sex hormones as risk predictors for common cancers in older men remains uncertain. This study was performed to assess associations of testosterone (T), dihydrotestosterone (DHT) and estradiol (E2), with incident prostate, lung and colorectal cancer in community-dwelling older men. Plasma T, DHT and E2 were assayed using liquid chromatography-mass spectrometry between 2001 and 2004 in 3690 men. Cancer outcomes until 20 June 2013 were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 44 publications
(36 reference statements)
4
24
1
Order By: Relevance
“…Overall, these studies of men treated with supraphysiologic doses of DHT do not support the hypothesis that modest elevations of DHT and DHT/T ratios observed with commonly used TRT preparations (including injectable T esters, transdermal T, and oral TU) will yield deleterious effects in men, particularly in androgen-sensitive tissues like prostate. Consistent with this conclusion are recent data from a longitudinal, observational cohort study of 3638 men in which circulating DHT (measured by LC-MS/MS) was not associated with incident prostate cancer (56).…”
Section: Serum Dht and Dht/t Ratios In Men After Transdermal Dht Admisupporting
confidence: 58%
“…Overall, these studies of men treated with supraphysiologic doses of DHT do not support the hypothesis that modest elevations of DHT and DHT/T ratios observed with commonly used TRT preparations (including injectable T esters, transdermal T, and oral TU) will yield deleterious effects in men, particularly in androgen-sensitive tissues like prostate. Consistent with this conclusion are recent data from a longitudinal, observational cohort study of 3638 men in which circulating DHT (measured by LC-MS/MS) was not associated with incident prostate cancer (56).…”
Section: Serum Dht and Dht/t Ratios In Men After Transdermal Dht Admisupporting
confidence: 58%
“…The impact of exogenous testosterone on cardiovascular risk remains controversial with multiple meta‐analyses showing a consistent but nonsignificant increased odds ratio, suggesting increased cardiovascular risk but which remains underestimated by so‐far underpowered analyses which also overlook transient temporal effects . Similarly, although endogenous testosterone levels appears unrelated to future development of prostate cancer, the impact of exogenous testosterone treatment that modestly increases serum PSA is less well established with meta‐analysis showing minimal short‐term risk but larger and longer‐term studies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration and invasion assays showed that 10μM T and 10μM E 2 promoted cells migration and invasion, and 50μM T and 50μM E 2 inhibited cells migration and invasion, when T and E2 concentrations were increased to 100μM, cells migration and invasion were promoted again( Fig.4 A,B). A recent study reported higher T predict increased incidence of lung cancer over the next decade in older men (Chan et al , 2017). Marsaud V reported that the effect of E 2 on ERα expression in lung cancer was also related to intervention time (Marsaud et al , 2003).…”
Section: Discussionmentioning
confidence: 99%